2015
DOI: 10.1111/aos.12780
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ketorolac 0.45% versus diclofenac 0.1% for macular thickness and volume after uncomplicated cataract surgery

Abstract: ABSTRACT.Purpose: To compare the effects of ketorolac 0.45% and diclofenac 0.1% on macular thickness and volume after uncomplicated cataract surgery. Methods: A total of 76 eyes of 76 patients who underwent uncomplicated cataract surgery were included. Patients were treated with either diclofenac 0.1% (38 eyes) or ketorolac 0.45% (38 eyes) after surgery. The macular thickness and volume were obtained with optical coherence tomography (OCT). Central subfield thickness (CST, OCT 1 mm zone), total foveal thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
5
1
1
Order By: Relevance
“…Macular volume parameters correlate well with visual acuity in a range of conditions including DME and retinal vein occlusion and are increasingly being used in clinical trials as a structural marker of disease activity and progression. 5,13,14 Our CR of TMV in uncorrected scan was higher than that previously reported, but there are relatively few reports of CR of TMV and our study was of a diverse group of patients defining general estimates of intersession repeatability. 8 Whilst there was little change in TMV after adjustment for segmentation error in eyes without macular disease, CRs for both drusen (0.45 to 0.18 mm 3 ) and AMD-geographic atrophy or IRDmacular atrophy (1.03 to 0.24 mm 3 ) was significantly reduced by manual segmentation correction.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Macular volume parameters correlate well with visual acuity in a range of conditions including DME and retinal vein occlusion and are increasingly being used in clinical trials as a structural marker of disease activity and progression. 5,13,14 Our CR of TMV in uncorrected scan was higher than that previously reported, but there are relatively few reports of CR of TMV and our study was of a diverse group of patients defining general estimates of intersession repeatability. 8 Whilst there was little change in TMV after adjustment for segmentation error in eyes without macular disease, CRs for both drusen (0.45 to 0.18 mm 3 ) and AMD-geographic atrophy or IRDmacular atrophy (1.03 to 0.24 mm 3 ) was significantly reduced by manual segmentation correction.…”
Section: Discussioncontrasting
confidence: 53%
“…We reported the intersession CR of TMV before and after manual correction as 0.62 and 0.16 mm 3 , respectively. Macular volume parameters correlate well with visual acuity in a range of conditions including DME and retinal vein occlusion and are increasingly being used in clinical trials as a structural marker of disease activity and progression . Our CR of TMV in uncorrected scan was higher than that previously reported, but there are relatively few reports of CR of TMV and our study was of a diverse group of patients defining general estimates of intersession repeatability .…”
Section: Discussionmentioning
confidence: 42%
“…Other authors found no significant differences between diclofenac 0.1% and ketorolac 0.45% groups in macular thickness 1 month after uneventful surgery. 49 However, at the second postoperative month, the ketorolac group had significantly lower central subfield thickness than the diclofenac group. Wang et al 50 compared the efficacy of bromfenac 0.1% administered twice daily for 4 weeks, bromfenac 0.1% administered twice daily for 8 weeks, fluorometholone 0.1% administered three times daily for 4 weeks, and dexamethasone 0.1% administered three times daily for 4 weeks.…”
Section: Pcme Preventionmentioning
confidence: 84%
“… 2 , 45 , 65 In addition, there is no commonly accepted method of reporting OCT-based PCME, which hinders the assessment of treatment outcomes. 28 , 49 , 50 Third, some studies may have favored NSAID treatment by preferential pretreatment with NSAIDs in one study arm. 28 , 45 , 47 , 51 In other studies, no adjustment was made for dosing disparities between groups treated with a corticosteroid alone and with the combination of a NSAID and a corticosteroid.…”
Section: Critical Summarymentioning
confidence: 99%
“…Lee et al [ 24 ] reported that following uncomplicated cataract surgery, topical ketorolac 0.45% was more effective than diclofenac 0.1% in preventing increases in macular thickness and volume. They observed that two months after surgery, the ketorolac group had significantly lower total foveal thickness, total macular thickness, and average macular thickness than the diclofenac group.…”
Section: Discussionmentioning
confidence: 99%